Giant cell lesion and traumatic bone cyst: pathologically related lesions? - Prunes, Bianca de Bem; Daroit, Natália Batista; Nunes, Júlia Silveira; Cunha Filho, Joao Júlio da; Rados, Pantelis Varvaki; Visioli, Fernanda (Journal of Oral Diagnosis, 2019)
Introduction: Synchronous lesions of the jaws are reported in the literature and the etiopathogenesis can be similar in some cases. The oral surgeon must know the diseases that may occur simultaneously. Objective: The aim of this study was to report a case of synchronous lesions, your management, additionally discuss the etiopathogenesis correlation among these lesions and the possible evolution from one disease to the other in order to aid the professional about the management of this occurrence. Methods: This study reported a case of a 14-year-old female patient presenting a reddish sessile nodule in mandibular left premolars gingival region. Results: Radiographically, a well-defined radiolucent area involving left mandibular body was observed. An incisional biopsy of the extra-osseous lesion was performed and a giant cell lesion was histopathologically diagnosed. A surgical bone exploratory procedure revealed an empty cavity; therefore curettage to stimulate bleeding was performed in addition to the extra-osseous lesion excision. The final diagnosis was synergistic peripheral giant cell lesion and traumatic bone cyst. The 12 months follow-up did not show any relapse, moreover, the complete bone neoformation was observed. Conclusions: The pathogenesis of both lesions remains uncertain and a complete and detailed clinical and histopathological examination added to rigorous follow up with image exams resulted in a correct diagnosis and good prognosis of this case.